Realization of High-End Multiplexers and Demultiplexers using CSWAP Quantum Gate - A. Reshma Priamvada (Journal of Electronic Design Engineering, 2021)
CMOS technology is expected to come to an end in performance and accuracy due to limitations of the shirking of the transistors. To overcome these limitations, researchers are working towards the development of quantum circuits that provide high-speed processing. In this work, high-end quantum multiplexer and demultiplexer circuits are proposed using a controlled SWAP (CSWAP) gate with low quantum cost. The proposed circuits are implemented using quantum gates and simulated to reduce complexity and improve performance. The software tool used for the design and simulation of the proposed structures is IBM Qiskit with python coding. It is observed from the simulation results that the proposed multiplexers are improved by more than 28% compared with the existing designs available so far in the literature.